Ni-catalyzed highly enantioselective synthesis of sulfur protected P-stereogenic supramolecular phosphine - Koshti(S), Vijay S.; Chandanshive, Amol C.; Mote, Nilesh R.; Chikkali, Samir H. (Journal of Chemical Sciences, 2021)
As phosphines readily invert, the synthesis of P-chiral phosphines is a challenging task and has been rarely investigated. We report the synthesis of a nickel complex [Ni-((S,S)Me-FerroLANE)(phenyl)(I)] (Ni-Cat.1) and its performance in a P-C coupling reaction to generate P-chiral phosphine. The Ni-Cat.1 was synthesized by mixing ligand (S,S) Me-FerroLANE with the metal precursor [(diphenylphosphanyl)nickel(phenyl)(I)] in good yield. Ni-Cat.1 was characterized using different spectroscopic and analytical techniques. Treatment of racemic methyl(phenyl)phosphine (1) with 1-(3-iodophenyl)urea (2) produced the corresponding P-chiral supramolecular phosphine (3). Optimization of reaction parameters produced sulfur protected phosphine N-(3-(methyl(phenyl)phosphorothioyl)phenyl)formamide (3') with excellent enantiomeric excess (99% ee) and moderate conversion (51%).
Keywords: Asymmetric synthesis; Nickel catalyst; P-C coupling; P-Stereogenic phosphine; supramolecular ligands